Pengembangan Desa Berkelanjutan Melalui Pengelolaan Lingkungan, Digitalisasi UMKM, dan Edukasi Masyarakat di Desa Kedung Pengawas Rw 13 Kecamatan Babelan, Kabupaten Bekasi - Alfanda Refandiasworo; Alluf Luqman Raasyid; Anantha Adetya Putra; Aulia Aishiteri Angelin; Azzahra Octarina; Cornelius Parulian Sinurat; Faris Gromiko; Muhammad Rafi Sujud; Naelis Suhada; Nur Aulia Kamilah; Reskal De Perta; Salsa Paulina Rahman; Wulandari Muazizah; Yudo Arsya Ramadhan (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Community Service Program (KKN) is a form of community engagement that aims to implement students’ knowledge and skills within society. KKN Group 80 of Universitas Bhayangkara Jakarta Raya was conducted in Kedung Pengawas Village, Babelan District, Bekasi Regency, with a focus on enhancing community participation through educational activities, MSME development, and environmental awareness. The implemented programs included children’s creativity development activities, public health awareness programs, assistance for micro-enterprises through promotional media strengthening and QRIS digital payment socialization, as well as community-based environmental clean-up activities. The implementation method consisted of observation, coordination with village officials, participatory program implementation, and activity evaluation. The results indicated that the children’s creativity development activity involved 40 participants, the public health awareness activity involved 16 residents, the micro-enterprise assistance program involved 5 MSME owners with 3 business owners expressing interest in adopting QRIS, and the environmental clean-up activity involved 20 residents and 14 KKN students. The programs received positive responses from the community and contributed to improving children’s creativity, public health awareness, MSME owners’ understanding of digital technology utilization, and environmental cleanliness awareness.